The availability, cost, and affordability of essential medicines for asthma and COPD in low-income and middle-income countries: a systematic review - Marie Stolbrink, BMBCh; Helen Thomson, MBChB; Ruth M Hadfield, PhD; Obianuju B Ozoh, PhD; Rebecca Nantanda, PhD; Shamanthi Jayasooriya, PhD; Brian Allwood, PhD; David M G Halpin, ProfDPhil; Sundeep Salvi, PhD; Maria Montes de Oca, ProfPhD; Kevin Mortimer, ProfPhD; Sarah Rylance, PhD (Elsevier, 2022)
Summary: Background: Asthma and chronic obstructive pulmonary disease (COPD) cause a considerable burden of morbidity and mortality in low-income and middle-income countries (LMICs). Access to safe, effective, quality-assured, and affordable essential medicines is variable. We aimed to review the existing literature relating to the availability, cost, and affordability of WHO's essential medicines for asthma and COPD in LMICs. Methods: A systematic review of the literature was done by searching seven databases to identify research articles published between Jan 1, 2010, and June 30, 2022. Studies on named essential medicines for asthma and COPD in LMICs were included and review articles were excluded. Two authors (MS and HT) screened and extracted data independently, and assessed bias using Joanna Briggs Institute appraisal tools. The main outcome measures were availability (WHO target of 80%), cost (compared with median price ratio [MPR]), and affordability (number of days of work of the lowest paid government worker). The study was registered with PROSPERO, CRD42021281069. Findings: Of 4742 studies identified, 29 met the inclusion criteria providing data from 60 LMICs. All studies had a low risk of bias. Six of 58 countries met the 80% availability target for short-acting beta-agonists (SABAs), three of 48 countries for inhaled corticosteroids (ICSs), and zero of four for inhaled corticosteroid-long-acting beta-agonist (ICS-LABA) combination inhalers. Costs were reported by 12 studies: the range of MPRs was 1·1-351 for SABAs, 2·6-340 for ICSs, and 24 for ICS-LABAs in the single study reporting this. Affordability was calculated in ten studies: SABA inhalers typically cost around 1-4 days' wages, ICSs 2-7 days, and ICS-LABAs at least 6 days. The included studies showed heterogeneity. Interpretation: Essential medicines for treating asthma and COPD were largely unavailable and unaffordable in LMICs. This was particularly true for inhalers containing corticosteroids. Funding: WHO and Wellcome Trust.